Analisis Kinerja Pelayanan Bus Trans Metro Dewata Saat Pandemi Berdasarkan Pedoman Departemen Perhubungan - Hidayat, Dwi Wahyu; Satwika Gayatri, Ni Komang; Soimun, Ahmad; Ahmad, Rahmat (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
Public transportation was an activity of transferring people or goods from one place to another using a public transportation system to pay a certain amount of money. In the Bali public transport provided by the government is trans metro dewata, which is an attempt by the government to reduce the use of private vehicles. Business screens allow one bus ride to hold as many as one to two passengers. The aim of this study is to understand the quality of the metro bus service of the dewata particularly during the elections, so as to give public an idea of the quality of the metro bus service of the dewata. Based on the fourth parameters conducted on the quality of service according to the department of transportation, lectures on metro metro bus services have been very good, and it can inform the public that the quality of bus service when the pandemic pandemic has not dropped.